2003
DOI: 10.1074/jbc.m208249200
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Polyamines Promote the Aggregation of α-Synuclein

Abstract: The cellular polyamines putrescine, spermidine, and spermine accelerate the aggregation and fibrillization of ␣-synuclein, the major protein component of Lewy bodies associated with Parkinson's disease. Circular dichroism and fluorometric thioflavin T kinetic studies showed a transition of ␣-synuclein from unaggregated to highly aggregated states, characterized by lag and transition phases. In the presence of polyamines, both the lag and transition times were significantly shorter. All three polyamines acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
189
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(205 citation statements)
references
References 61 publications
14
189
1
1
Order By: Relevance
“…A previous study showed that PD patients have elevated levels of spermidine and spermine in red blood cells (13), which do not themselves produce polyamines. Another study showed that in an in vitro system, exogenously added spermidine and spermine accelerate the aggregation of α-synuclein (12). Furthermore, previous studies have shown that SAT1 is expressed in numerous brain regions implicated in PD, including the substantia nigra pars compacta (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study showed that PD patients have elevated levels of spermidine and spermine in red blood cells (13), which do not themselves produce polyamines. Another study showed that in an in vitro system, exogenously added spermidine and spermine accelerate the aggregation of α-synuclein (12). Furthermore, previous studies have shown that SAT1 is expressed in numerous brain regions implicated in PD, including the substantia nigra pars compacta (33).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies have suggested that polyamines increase the aggregation of α-synuclein (12,15,16). To investigate the relationship between polyamines and α-synuclein in an in vivo system, we turned to an established yeast model of α-synuclein toxicity (17).…”
Section: Yeast Studies Establish a Link Between Polyamines And α-Synumentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological polyamines (putrescine, cadaverine, spermidine, and spermine), the naturally occurring di, tri-, and tetra amines, are closely related to neuronal cell biochemical activity in the brain, including interaction with neurotransmitter receptors such as the Nmethyl-D-aspartate receptor, regulation of substances in degenerating cells, ion channels such as K + and protection of neuronal cells from oxidative damage [5][6][7][8][9][10]. Additionally, administration of spermine reduces infarction in cerebral ischemic rat models [11], although the systemic role of altered PAs has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…These vectors drive the expression of poly-His-tagged and non-tagged ␣-synuclein, respectively (38). His-tagged ␣-synuclein protein was expressed and purified as described previously for tau protein (38), whereas non-tagged ␣-synuclein was prepared as in Antony et al (31) except that Mono Q chromatography was used as the anion exchange resin. Because these preparations behaved similarly in all assays described below, the His-tagged form was used for experimentation for ease of preparation.…”
Section: Materials-arachidonicmentioning
confidence: 99%